(untitled) (Research, Society and Development, 2022)
Shaft sinking is a classic activity in underground mines. In shafts with small cross-section or in mines with low mechanization indices it is common to use hand pneumatic drills and blasting by explosive gelatin in cartridges, employing natural draft or flexible ducts with axial fans for gases and fumes exhaustion, muck removal by hand shoveling into hoistable dumping buckets. System of this type has been studied here, consisting of a rectangular cross-section shaft (3.7 m x 2.0 m), with final depth of 94 m, excavated in order to obtain samples for a pilot-scale mineral processing testwork, before the open pit mine’s industrial startup. The shaft had a concrete collar and its walls were supported by wooden sets spaced 1.5 m and 25 mm thick wooden planks as liners. This shaft has been excavated in schist rocks belonging to the metamorphosed hydrothermal deposit of copper and gold located in Chapada (municipality of Mara Rosa, Brazil). Daily production worksheets covering one month campaign were statistically analyzed, encompassing the entire cycle of mining operations, namely drilling, charging and blasting, fumes exhaustion, mucking, wall and face trimming and scaling, and assemblage of support system. Operation downtimes were also quantified. Statistical analysis of productivity indices allowed the detection of critical points of the operation and the establishment reference for similar mining operations.